2020
DOI: 10.2196/16251
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of a Multilevel Mobile Health App for Substance Use, Sexual Risk Behaviors, and Testing for Sexually Transmitted Infections and HIV Among Youth: Randomized Controlled Trial

Abstract: Background Preventing and reducing substance use disorders, sexually transmitted infections (STIs)/HIV, and teen pregnancy, and the associated risk behaviors (ie, substance use and sexual risk behaviors) among youth remain public health priorities in the United States. Equally important is improving the uptake of STI/HIV testing among the youth. Mobile health (mHealth) apps may be a solution to ameliorate these public health concerns; however, few mHealth preventive interventions have demonstrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 41 publications
3
38
0
1
Order By: Relevance
“…Studies with less than a 100% consent rate have the potential for selection bias of participants. The studies’ response rates, defined as eligible participants consented to participate, were 85% [ 48 ], 64% [ 49 ], 47% [ 50 ], 35% [ 51 ], and 24% [ 52 ]. The response rates were not provided by three studies reducing ability to assess selection bias [ 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with less than a 100% consent rate have the potential for selection bias of participants. The studies’ response rates, defined as eligible participants consented to participate, were 85% [ 48 ], 64% [ 49 ], 47% [ 50 ], 35% [ 51 ], and 24% [ 52 ]. The response rates were not provided by three studies reducing ability to assess selection bias [ 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…High retention rates were achieved by two studies, reported as 98% [ 52 ] and 96% [ 49 ], reducing the selection bias in the analysis. Moderate retention rates were achieved at 79% [ 48 ] and 68% was reported by two studies [ 50 , 51 ].The Thai-based community cluster RCT study used a second random sample for the follow-up survey from the intervention and control communities, and therefore retention rates were not applicable [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The app, developed in Spain, consists of a brief risk behaviour survey and targeted interactive content based on the youth's specific risk behaviours. The app was developed together with youth, and small-scale feasibility studies of the app have shown promising results, including more youth-clinician risk communication [85].…”
Section: Sexual Risk Assessmentsmentioning
confidence: 99%
“…27 mHealth has been shown to facilitate access to health care and health-related information, promote communication with health care professionals, and improve healthy lifestyle behaviors and sexual attitudes among underserved and transient youth populations. [28][29][30][31][32][33][34][35] These advantages, coupled with most youths' familiarity with technology, 36 illustrate the potential for mHealth applications to be effective in supporting the delivery of services to youth with histories of CSE. Although concerns regarding access to technology among underserved populations exist, available research consistently documents that individuals in underserved communities frequently access the Internet and use mobile devices, 32,[37][38][39] including youth seeking health-related information.…”
mentioning
confidence: 99%